Kelayakan Produk Aksesoris Rambut Ramah Lingkungan Berbahan Dasar Limbah Pelepah Batang Pohon Pisang - Ratih Wijayanti; Ifa Nurhayati (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
Banana tree stem waste has the potential to be used as a raw material for environmentally friendly hair accessories, but its utilization is still limited. This study aims to analyze the product validity and user preference level for three models of hair accessories made from banana tree stem waste. The study used a quantitative approach with a pre-experimental one-shot case study design. The product validity was tested by three expert panelists, while the preference test involved 20 respondents. Data were analyzed using descriptive percentage analysis. The results of the study showed that in the validity test, each assessment indicator of shape, neatness, strength, color, and final result showed a percentage above the very valid criteria limit. Models P2 and P3 obtained the highest average score (92.50%), followed by P1 (90.00%), which indicates that banana tree stem material has adequate structural characteristics to support the function and aesthetics of hair accessories. The results of the preference test also showed a very high level of user acceptance for all indicators, shape, strength, aesthetics, neatness, ease of application, and final result. Model P2 achieved the highest average score (88.61%), followed by P1 (88.33%), and P3 (88.06%). This finding confirms that the product is not only technically feasible according to experts but also highly accepted by users in terms of comfort, aesthetics, and ease of use.